A Theory of Compliance with Minimum Wage Law - Simplice A. Asongu; Mohamed Jellal (African Governance and Development Institute (AGDI), 2014)
Purpose In this paper, we introduce firm heterogeneity in the context of a model of non-compliance with minimum wage legislation. Design/methodology/approach Theoretical modeling under government compliance policy and wages & employment under non compliance. Findings The introduction of heterogeneity in the ease with which firms can be monitored for non compliance allows us to show that non-compliance will persist in sectors which are relatively difficult to monitor, despite the government implementing non stochastic monitoring. Moreover, we show that the incentive not to comply is an increasing function of the level of the minimum wage and increasing function of the gap between the minimum wage and the competitive wage rate. Originality/value We have shown why non compliance persists in certain sectors of activity despite frequent inspection by government agencies.
Keywords: H26; O17; 330; Minimum; wage; legislation; informal; sector; in; LDCs